Role of Transactional and Relational Contract in Employee Turnover Intention (A Study of Business Affiliated Institutions Employees of Peshawar Pakistan) - Khan, Shahzad; Shahzad, Saqib; Ullah, Raza; Khan, Qaiser; Wasim, Danish (Journal of Asian Business Strategy, 2012)
The aim of this research was to investigate the impact of transactional and Relational contract on turn over intention in employees of Peshawar University business affiliated institutions in region of Peshawar Pakistan. The effect of both contracts on the turnover intention was investigated individually. A sample size of one hundred individuals was used in the study. For the analysis part of study hypothesis were developed and regression and correlation analysis was used. The study revealed that both relational and transactional contracts have an impact on turnover intention. But between both transactional and relational contracts transactional contract have more significant impact on turnover intention.